2016
DOI: 10.3904/kjim.2015.103
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate risk of multidrug-resistant organisms in patients who admitted intensive care unit with healthcare-associated pneumonia

Abstract: Background/Aims:Healthcare-associated pneumonia (HCAP) was proposed asa new pneumonia category in 2005, and treatment recommendations includebroad-spectrum antibiotics directed at multidrug-resistant (MDR) pathogens.However, this concept continues to be controversial, and microbiological data arelacking for HCAP patients in the intensive care unit (ICU). This study was conductedto determine the rate and type of antibiotic-resistant organisms and theclinical outcomes in patients with HCAP in the ICU, compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…[ 2 , 6 , 10 , 19 ] Moreover, increased mortality in HCAP patients was also shown to be related to underlying patient-related factors and the severity of illness, rather than the presence of CAP-DRPs or IIAT. [ 11 , 19 , 20 ] A cohort study conducted at 346 United States hospitals found no evidence that guideline-based antimicrobial therapy reduced mortality in HCAP patients. [ 21 ] It is increasingly recognized that comorbidities account for a large proportion of mortality in patients with HCAP and a significant proportion of this mortality cannot be prevented by antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 , 6 , 10 , 19 ] Moreover, increased mortality in HCAP patients was also shown to be related to underlying patient-related factors and the severity of illness, rather than the presence of CAP-DRPs or IIAT. [ 11 , 19 , 20 ] A cohort study conducted at 346 United States hospitals found no evidence that guideline-based antimicrobial therapy reduced mortality in HCAP patients. [ 21 ] It is increasingly recognized that comorbidities account for a large proportion of mortality in patients with HCAP and a significant proportion of this mortality cannot be prevented by antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, our pathogen identification rate (38.3%) was higher than those reported previously. [ 13 , 20 ] Third, the microbiologic data were obtained mainly from sputum cultures, and were semiquantitative. Hence, their accuracy is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the distribution of multi-drug resistant bacteria in RICU was significantly higher than that in the non-ICU respiratory departments. On one hand, the patients in RICU with severe disease, including cancer, kidney failure, heart disease, chronic obstructive pulmonary disease, etc., were commonly prescribed broad-spectrum antibiotics for empirical therapy, posing the risk of MDR bacterial infections to patients (21)(22)(23). On the other hand, the risk of ventilator-associated pneumonia (VAP) increased due to the prolonged hospitalization in ICU and routine invasive procedures such as intubation and respiratory support.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, causative agents of CAP were identified using conventional culture methods, so microorganisms were identified in less than 30% of CAP cases during the pre-PCV7 period [3940414243]. With advances in serological and molecular diagnostic tests, the diagnostic yield has improved by up to 40-50%, yet around 50% of CAP pathogens are still unidentified (Table 2) [744454647]. Prior antibiotic use is one of the important reasons for test-negative results.…”
Section: Etiologic Distribution Of Causative Pathogens In Community-amentioning
confidence: 99%
“…Among CAP cases caused by identified bacterial pathogens, S. pneumoniae is the most important causative species, accounting for 26.9–69.4% of pneumonia cases in South Korea (Table 2) [48], and the proportion of pneumococcal pneumonia was higher in studies confined to older adults [749]. However, in a study of severe CAP cases admitted to intensive care units (ICUs), S. aureus infection was more common compared to S. pneumoniae (37.8% vs. 13.5%) [46]. Etiologic distribution might be affected by disease severity, age, and underlying medical conditions.…”
Section: Etiologic Distribution Of Causative Pathogens In Community-amentioning
confidence: 99%